Destemidos, rebeldes e andarilhos: a população negra livre e pobre no cotidiano da cidade da Parahyba do Norte (1850 – 1867) - Gomes, George Henrique de Vasconcelos (2020)
The present academic work was developed in association with the History Program (Master Program) of the Federal University of Paraiba, Brazil, on the “History and Regionalism” line of research and has the objective to present and discuss the social complexity of the Free Black and Poor Population at the City of Parahyba at the 19th century. This complexity is understood here as being a variability of social relationships that had been established between these free black and poor individuals and their slaved brothers as well as the individuals that belong to other social categories, living together and sharing experiences at this part of the Province of Paraiba. The development of this study was possible due to the necessity of a more careful analysis of some gaps in the historiography of Paraiba with regard to the free black and poor population at the Province of Paraiba in the 19th century. This work will be guided by the perspectives from Edward Palmer Thompson and his concept of Experience, as well as various kinds of primary historical sources from the period in question. At the same time, we count with the support of documentation such as Passports, baptism records from the N.S. das Neves church, nominal lists, presidential province reports, provincial health ombudsman reports from Paraiba, police office reports, the classic and recent bibliography and the newspapers that were produced at the Paraiba Province between 1850 and 1867. These sources made possible to us to comprehend the period and helped to identify aspects of the everyday life and other experiences from the free black and poor population, as well as their paths between the villages and towns of the province of Paraiba and the trade with other provinces witch as possible due to the presence of this population on that society. From the analysis, cataloguing and crossing of the mentioned sources, it was possible to observe a significant part of the everyday practices of that social group: their eating habits, housing, living conditions, sociability networks and the relations with other social segments.